Myocardial Steatosis Among Antiretroviral Therapy–Treated People With Human Immunodeficiency Virus Participating in the REPRIEVE Trial. (9th July 2020) - Neilan, Tomas G; Nguyen, Kim-Lien; Zaha, Vlad G; Chew, Kara W; Morrison, Leavitt; Ntusi, Ntobeko A B; Toribio, Mabel; Awadalla, Magid; Drobni, Zsofia D; Nelson, Michael D; Burdo, Tricia H; Van Schalkwyk, Marije; et al.
Abstract: Background: People with human immunodeficiency virus (PWH) face increased risks for heart failure and adverse heart failure outcomes. Myocardial steatosis predisposes to diastolic dysfunction, a heart failure precursor. We aimed to characterize myocardial steatosis and associated potential risk factors among a subset of the Randomized Trial to Prevent Vascular Events in HIV (REPRIEVE) participants. Methods: Eighty-two PWH without known heart failure successfully underwent cardiovascular magnetic resonance spectroscopy, yielding data on intramyocardial triglyceride (IMTG) content (a continuous marker for myocardial steatosis extent). Logistic regression models were applied to investigate associations between select clinical characteristics and odds of increased or markedly increased IMTG content. Results: Median (Q1, Q3) IMTG content was 0.59% (0.28%, 1.15%). IMTG content was increased (> 0.5%) among 52% and markedly increased (> 1.5%) among 22% of participants. Parameters associated with increased IMTG content included age ( P = .013), body mass index (BMI) ≥ 25 kg/m 2 ( P = .055), history of intravenous drug use (IVDU) ( P = .033), and nadir CD4 count < 350 cells/mm³ ( P = .055). Age and BMI ≥ 25 kg/m 2 were additionally associated with increased odds of markedly increased IMTG content ( P = .049 and P = .046, respectively). Conclusions: A substantial proportion of antiretroviral therapy–treated PWH exhibited myocardial steatosis. Age, BMI ≥ 25 kg/m 2, low nadir CD4 count, and history of IVDU emerged as possible risk factors for myocardial steatosis in this group. Clinical Trials Registration: NCT02344290; NCT03238755.